Population structure and selective signature analysis of local sheep breeds in Xinjiang, China based on high-density SNP chip - Yanhao Li; Xiaopeng Li; Zhipeng Han; Ruizhi Yang; Wen Zhou; Yuwei Peng; Jianzhong He; Shudong Liu (Scientific Reports)
Abstract The frigid and droughty climate of Xinjiang in China has given rise to unique indigenous sheep breeds with robust adaptability and resistance. To investigate the genetic mechanism of adaptability of Xinjiang sheep to the local extreme environment, we conducted population genetic structure analyses for three native Xinjiang sheep breeds: Altay sheep (ALT), Bashbay Sheep (BSBC), and Duolang sheep (DLC), as well as two foreign sheep breeds: Suffolk and Dorset, using the Ovine Infinium HD SNP BeadChip(680 K). Our findings revealed distinct genetic and evolutionary histories between Xinjiang and foreign sheep breeds. Principal Component Analysis (PCA) and phylogenetic tree effectively differentiate these five sheep breeds based on their geographical origins, and the domestication level of Xinjiang sheep is comparatively lower than that of foreign sheep breeds. Furthermore, by utilizing three selective signature methods, namely Fixation Index (Fst), Cross Population Extended Haplotype Homozygosity Test (XP-EHH), and Nucleotide Diversity (π), we have successfully identified 22 potential candidate genes. Among these genes, there are TBXT, PDGFD, and VEGFA, which are closely related to tail type and lipid metabolism; VIL1, SLC11A1, and ZBTB46, which are associated with immune function; and candidate genes such as BNC1, HDAC1, and BMP5, which impact sheep reproductive traits. This study establishes a foundation for conserving and utilizing local sheep germplasm resources in Xinjiang and provides molecular insights into the genetic mechanisms governing sheep adaptation to extreme cold and arid environments.